Strategi Pengembangan Kompetensi Aparatur Sipil Negara dalam Mewujudkan World Class Government - Fitria Fitria; Suryanto Suryanto; Moch Ali Mashuri (Universitas Musamus, Merauke, Papua, 2022)
The importance of organizations in developing competency-based human resources on an ongoing basis is due to demands and changes in reform, for this reason a competency development strategy is needed for the State Civil Apparatus in realizing world class government in the current covid-19 pandemic era. The purpose of this study is to identify the strategy carried out by the Human Resources Development Agency of East Java Province in developing the competence of the State Civil Apparatus to realize world class government in the province of East Java during the Covid-19 pandemic era. This research method used is a qualitative method with data collection techniques through literature studies. The results showed that the strategy for competency development carried out in the era of the covid-19 pandemic was through a training and development program for the State Civil Apparatus based on the corporate university of the State Civil Apparatus. In the State Civil Apparatus corporate university program, employees can access and do internships according to the desired competencies. In addition, this State Civil Apparatus corporate university is integrative, flexible, participatory and sustainable so that it can accelerate the achievement of world class government in the East Java Province. This corporate university can create a link and match between competency improvement and organizational goals so that it is not solely in improving employee competencies, but at the same time achieving organizational goals.